Brain Drain Indonesia dan Dampaknya Bagi Indonesia - Santoso, Edy; Muslihatinningsih, Fivien; Zainuri (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
The purpose of this study is to analyze the effect of per capita income and the level of security in Singapore, Thailand and Malaysia on the brain drain of Indonesia and to find out how the impact of brain drain on Indonesia. The research method used is descriptive quantitative and uses panel data regression analysis. Based on the model specification test that has been carried out using the Chow test and the Hausman test, both suggest using the fixed effect model. The results show that the per capita income of Singapore, Malaysia and Thailand has a negative and significant effect on Indonesia's brain drain. The income of the destination area is a pull factor for the occurrence of brain drain, but if the government has increased domestic wages, it can reduce brain drain. The level of security in Singapore, Thailand and Malaysia has a negative and insignificant effect on brain drain in Indonesia, although the level of security is high in these countries, it does not necessarily guarantee legal protection for Indonesian workers who work there. If the brain drain continues, it will have a bad impact on Indonesia. Indonesia will lack a highly educated, expert or skilled workforce, so that Indonesia will be left far behind other countries in terms of economy, social and knowledge. For this reason, policies that support the development of domestic human resources are needed.